Spatio-temporal changes of coastline in Jiaozhou Bay from 1987 to 2022 based on optical and SAR data - Zhu, Yuandong; Li, Zhenjin; Zhao, Zheng; Lu, Lijun; Yang, Shucheng; Wang, Zhiyong (Frontiers in Marine Science, 2023)
In the past 35 years, the natural coastline along Jiaozhou Bay has undergone extensive changes under the influence of human activities, and the coastal wetland area has been drastically reduced. Therefore, it is of great importance to study the spatio-temporal changes, trends and causes of Jiaozhou Bay coastline for sustainable economic development and rational utilization of coastal resources. This paper constructed a comprehensive method for extracting the coastline information and change analysis based on long time series remote sensing data. Based on multi-spectral optical data and dualpolarization SAR data The results show that: 1) Coastline type information provides important information for analyzing the coastline changes in long time series, and it can effectively extract coastline information using multispectral optical data and dual-polarization SAR data. When the resolution of remote sensing data is 30m, the average error of the two types of data is better than one pixel, and the error between the data is about 1-2 pixels. 2) Based on the U-Net model, the overall accuracy of coastline classification using multi-spectral optical data and dual-polarization SAR data is 94.49% and 94.88%, respectively, with kappa coefficients of 0.9143 and 0.8949. 3) In the past 35 years, Jiaozhou Bay area has shown an obvious trend towards the ocean, with an average annual expansion of 16.723m. 4) The coastline of Jiaozhou Bay area is dynamic. Due to the frequent human activities, the coastline has been reconstructed on a large scale, and the length of artificial coastline has increased significantly. The proportion of artificial coastline length has increased from 33.72% in 1987 to 59.33% in 2022. 5) In the past thirty-five years the land reclamation area has reached 41.45km 2 , of which Shibei District, Licang District and Huangdao District are the three most frequent areas, with an area of 34.62 km 2 .